2020
DOI: 10.3390/ijms21113854
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of Mesenchymal Stromal Cell Transcriptome Persists even after Treatment in Patients with Multiple Myeloma

Abstract: Introduction. Multiple myeloma (MM) is a B-cell neoplasm characterized by clonal expansion of malignant plasma cells (MM cells) in the bone-marrow (BM) compartment. BM mesenchymal stromal cells (MSC) from newly diagnosed MM patients were shown to be involved in MM pathogenesis and chemoresistance. The patients displayed a distinct transcriptome and were functionally different from healthy donors’ (HD) MSC. Our aim was to determine whether MM–MSC also contributed to relapse. Methods. We obtained and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Notably, due to the pivotal role in the hematopoietic microenvironment and dual immunomodulatory capacity, more and more literatures have emerged to elucidate the potential pathogenesis of MSCs in a variety of disorders such as aplastic anemia [18], acute myelogenous leukemia [17], and type 2 diabetes mellitus [20]. For instance, Spelat et al and Lemaitre L et al respectively suggested the involvement of the cytokines (e.g., IL-6, IL-10) in secretome and transcriptome for MM development via facilitating MM cell proliferation [38,39]. As to MM, talented pioneers in the field have also indicated the diverse abnormalities in the cellular phenotype and distinct genomic profile to a certain extent [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, due to the pivotal role in the hematopoietic microenvironment and dual immunomodulatory capacity, more and more literatures have emerged to elucidate the potential pathogenesis of MSCs in a variety of disorders such as aplastic anemia [18], acute myelogenous leukemia [17], and type 2 diabetes mellitus [20]. For instance, Spelat et al and Lemaitre L et al respectively suggested the involvement of the cytokines (e.g., IL-6, IL-10) in secretome and transcriptome for MM development via facilitating MM cell proliferation [38,39]. As to MM, talented pioneers in the field have also indicated the diverse abnormalities in the cellular phenotype and distinct genomic profile to a certain extent [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SSPC gene expression is largely altered by MM, as demonstrated by in vitro co-culture studies of SSPCs with MM cell lines [114,115]. Even after ex vivo expansion of SSPCs without MM cells, the gene expression profiles of SSPCs from patients with MM are distinguishable from SSPCs from patients with premalignant monoclonal gammopathy of undetermined significance (MGUS; an asymptomatic condition that precedes MM) and healthy donors [114,[116][117][118][119]. Deregulated transcriptional pathways include cell cycle regulation, osteoblast maturation, MM cell survival factors, and immune-modulating factors [117,119].…”
Section: Targeting the Microenviromentmentioning
confidence: 99%
“…Deregulated transcriptional pathways include cell cycle regulation, osteoblast maturation, MM cell survival factors, and immune-modulating factors [117,119]. The deregulation of gene expression in SSPCs persists after anti-myeloma therapy [113,118,119], even in patients who are negative for measurable residual disease [119], suggesting a permanent modulation of the cells. This is supported by findings of genomic alterations [120] and epigenetic modifications of the SSPC genomes in MM, dependent on disease stage and inducible by MM cell co-culture [121].…”
Section: Targeting the Microenviromentmentioning
confidence: 99%
“…In detail, Schinke et al identified a prognostic MSC three-gene score, including collagen type IV alpha 1 (COL4A1), natriuretic peptide receptor 3 (NPR3), and integrin beta like 1 (ITGBL1), which is able to predict progression-free survival in MM patients and the progression of MGUS/SMM to MM [161]. Of note, as MSCs from patients who underwent completed treatment show a transcriptome essentially identical to that of patients at diagnosis, persistent printing could maintain a niche prone to relapse [163]. Single-cell sequencing also confirmed that current antitumor therapy fails to counteract MSC inflammation, highlighting their role in disease persistence [164].…”
Section: Role Of Mscs In In Multiple Myelomamentioning
confidence: 99%
“…As the immunological dysfunction of MSCs was observed already in SMM stromal cells but not in MGUS ones, the activation of an MSC-induced immunosuppressive microenvironment might contribute to the transition from MGUS to MM as an evolutionary advantage acquired during the multistep development of MM. Of note, MSCs from relapsed patients have an increased immunosuppressive ability compared to those from patients in remission [163]. The support of malignant clone proliferation by MM-MSCs is mediated by the stromal activation of the PD1/PDL-1 axis, disrupting T cell immune response [171,172].…”
Section: Role Of Mscs In In Multiple Myelomamentioning
confidence: 99%